THE BAD IMPACT OF PLASTIC WASTE ON THE CONSERVATION OF MARINE ANIMALS AS SOURCE OF INSPIRATION OF VECTOR ARTWORK - Prastyo, Nanda (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2020)
The purpose of this project is as one way to inform about the bad effects of plastic garbage on marine life to large community information sharing vision and mission, so it is expected to be able to educate and persuade viewers to contribute to the sustainability of the environment..The design of these vectors corresponds through several processes, with preliminary processes, pre-production, production and post-production. Technical aspects, aesthetic aspects and communication aspects provide coverage for analyzing these vector images. The vector’s image includes the purpose ofan informative message with the attraction of a combination of informative and emotionalattractiveness. It is manifested in the likeness of medium close up shot and naturalist descriptions that dominate in every area of the picture. The vector’s drawing uses applied principles as an effort to information, educate, and comunicate with the viewer feeds through the messages contained in the vector’s images